Protecting the Gulf's marine ecosystems from pollution - Abu-Zinada, A. H. (Birkhauser, 2008)
"This volume reviews present sources and levels of pollution in the Gulf, assesses their causes and effects on biota and ecosystems, and identifies gaps and obstacles currently preventing an effective integrated transboundary management of the marine and coastal resources."--Jacket